Pengembangan Media “Bingka Kentang” pada Pembelajaran Matematika untuk Siswa SDN 5 Baamang Hulu: Developing "Bingka Kentang" Media in Mathematics Learning for Students of SDN 5 Baamang Hulu - Dewi, Ayu Candra; Bulkani, Bulkani; Rahmaniati, Rita (Anterior Jurnal, 2025)
Learning media is important in increasing students' motivation and learning outcomes, especially in mathematics learning, which is often considered difficult. This study aims to develop the "Bingka Kentang" media (Creative and Fun Counting and Arranging Numbers) for mathematics learning on sequencing numbers for first-grade students using the ADDIE model at SDN 5 Baamang Hulu. This development research includes five stages: (1) Analysis, analyzing the needs and characteristics of students; (2) Design, designing media concepts; (3) Development, creating and validating media; (4) Implementation, implementing media in learning; and (5) Evaluation, evaluating the effectiveness of the media. The research subjects consisted of 30 first-grade students and two teachers. Research instruments include validation sheets, response questionnaires, observation sheets, and test questions. The results showed that the "Bingka Kentang" media met the validity criteria with a percentage of 87.25% (very valid) and received positive responses from teachers (90.5%) and students (93.2%). Implementing this media proved effective in increasing students' learning motivation, which was marked by an increase in the percentage of highly motivated students from 15% to 60%. This media also effectively improves understanding of sequencing numbers with an N-gain value of 0.59 (medium category) and classical learning completeness of 86.67%. The excellence of "Bingka Kentang" media lies in its integration with game elements suitable for first-grade students' characteristics.